On the Elliptic Problems Involving Multisingular Inverse Square Potentials and Concave-Convex Nonlinearities - Tsing-San Hsu (Abstract and Applied Analysis)
A semilinear elliptic problem (𝐸𝜆) with concave-convex nonlinearities and multiple Hardy-type terms is considered. By means of a variational method, we establish the existence and multiplicity of positive solutions for problem (𝐸𝜆).